Stylistic Analysis of the Eschatological Narrative in the Qur’an - Sholahudin, Shofwan; Sopian, Asep (Study Program of Arabic Language Teaching, 2025)
This study aims to analyze the stylistic aspects of Surah Az-Zumar verses 71–74, focusing on the eschatological representation of the Qur'an through linguistic elements. This study employs a qualitative approach, utilizing library research. The primary data consists of Surah Az-Zumar verses 71–74 and classical and modern exegeses collected through documentation. Data analysis uses qualitative content analysis based on the Qalyubi stylistic framework, encompassing phonological, morphological, syntactic, and semantic levels. Phonological analysis reveals a consistent end-rhyme pattern and internal rhythm, reinforced by assonance and tempo variations, which create significant emotional and aesthetic impacts. Morphologically, the strategic use of passive forms, such as